Effect of different cytokinin concentrations on establishing an in vitro micropropagation system for hop (Humulus lupulus L.) - Carloni, Edgardo José (2025)
Hops (Humulus lupulus L.) is a dioecious plant of the Cannabaceae family, highly valued in beer production. In vitro culture has been established as a tool in agricultural biotechnology for its propagation and improvement. This study evaluated the impact of different concentrations of cytokinins, to develop an efficient protocol for in vitro micropropagation of the species. Concentrations of 0.1, 1, 3, and 6 mg·L−1 of BAP and KIN and control without cytokinins were used. After 28 days of culture, growth and development variables were analysed. The results indicated that lower concentrations of cytokinins favoured most of the variables studied. In contrast, concentrations equal to or higher than 1 mg·L−1 of BAP and KIN reduced growth, and increased callus formation and hyperhydricity. The protocol developed proved efficient, with more than 90% of the explants generating at least two shoots and approximately the same percentage developing roots. In addition, seedlings obtained with the 0.1 mg·L−1 KIN and BAP treatment showed high survival after transplanting. Applying low concentrations of cytokinins eliminated the need for an additional rooting stage, optimising the micropropagation process